Alternatives to antibiotics for treatment of mastitis in dairy cows - Li, Xiaoping; Xu, Chuang; Liang, Bingchun; Kastelic, John P.; Han, Bo; Tong, Xiaofang; Gao, Jian (Frontiers in Veterinary Science, 2023)
Mastitis is considered the costliest disease on dairy farms and also adversely affects animal welfare. As treatment (and to a lesser extent prevention) of mastitis rely heavily on antibiotics, there are increasing concerns in veterinary and human medicine regarding development of antimicrobial resistance. Furthermore, with genes conferring resistance being capable of transfer to heterologous strains, reducing resistance in strains of animal origin should have positive impacts on humans. This article briefly reviews potential roles of non-steroidal anti-inflammatory drugs (NSAIDs), herbal medicines, antimicrobial peptides (AMPs), bacteriophages and their lytic enzymes, vaccination and other emerging therapies for prevention and treatment of mastitis in dairy cows. Although many of these approaches currently lack proven therapeutic efficacy, at least some may gradually replace antibiotics, especially as drug-resistant bacteria are proliferating globally.